Doppler Shift Based Low Earth Orbit Satellite Terminal Positioning Technology - WEI Fan; WANG Jikang; ZHAO Yuyan; LIAO Yucheng (天地一体化信息网络)
The integration of communication, navigation and remote sensing is the evolutinary direction for future low earth orbit (LEO) satellite Internet to achieve ubiquitous integrated space-based information service. To expand the utilities of existing communication constellations, a multi-satellite joint positioning scheme has been designed, which utilizes the Doppler shift carried by communication signals to obtain the geographical location information for target terminals. Furthermore, a practical Doppler shift estimation algorithm has been proposed, which can address the issue of LEO satellite Doppler shift exceeding the subcarrier spacing of OFDM system. Finally, through link-level simulation, the positioning performance of the proposed scheme for target terminal has been validated.